Socio-Cultural Dynamics of Pre-School Education in Nepal - Rupakheti, Ritu (Molung Educational Frontier, 2020)
The article ‘Socio-Cultural Dynamics of Pre-School Education in Nepal,’ explores the increasing trend of the Early Childhood Education (ECE) system in Kathmandu Valley, which is shaping the perspective of people on education, and in turn, the ways people’s attitude is reshaping this emerging ECE trend. The gradual breakdown of the conventional education approach and adoption of new system is in the liminal stage. Unplanned introduction of such education borrowed from different cultural contexts seems to generate a complex, and sometimes conflicting response from society. The fieldwork of this paper was carried out at Ravibhawan of Kathmandu Metropolitan City. Two Montessori-based pre-schools from the Ravibhawan area were chosen for this purpose. It follows the anthropological inquiry with descriptive and exploratory approach. Participant observation and the narratives of the informants constitute the basis of primary information. Both key informant interviews, and informal discussions are employed to explore the emic perspectives of the concerned. Government documents and other relevant literatures are the source of secondary information. Purposive sampling is the main basis of informant selection. This paper finds that there is a complicated and much-embedded relationship between pre-schooling, and the existing socio-cultural contexts of the communities. Several factors including the notion of family, gender roles, economic and social status, and the increasing global connectivity seem to be in complex interaction to influence the final choice of the parents. This study is a contribution towards the anthropology of pre-school education in Nepal. Despite the increasing importance of pre-school education, and its increasing trend in Nepal, anthropologists seem to be less interested in exploring this field.